Ergonomics assessment and intervention for handwheel valves operation process - Aldmour, Khaleel Mahmoud Hammoud (School of Manufacturing Engineering, 2019)
The scope of this research is limited to specific objectives for the process of opening and closing the handwheel valves and does not address other goals outside the research. Consequently, the scope of this research is restricted only to explore the presences of two ergonomics risk factors (i.e. awkward posture, forceful exertion) resulting from the process of opening and closing the handwheel valves and their effect in the prevalence of MSDs problems among the plant operators. Therefore, the research looking for applying ergonomics interventions for the process of opening and closing the handwheel valves to improve the process as well as alleviate the presence of ERFs (awkward posture, forceful exertion). On the other hand, the research covers this problem in one chemical industry, and the sample was only from the plant operators. Furthermore, the valves that have undergone for research have a diameter size between